Using a Bayesian Approach to Evaluating the Effectiveness of the Banking System Использование байесовского подхода к оценке эффективности банковской системы - Khayluk Svetlana A. (Problemi Ekonomiki, 2012)
The article introduces the concept of «likelihood of effective functioning of the banking system» as equivalent to the notion of «efficiency of the banking system». Demonstrate the use of the Bayesian approach to model evaluation of the effectiveness of the banking system and provides the basic elements of this model. В статье вводится понятие «вероятности эффективного функционирования банковской системы» как эквивалентное понятию «эффективности банковской системы». Обосновывается использование байесовского подхода в модели оценки эффективности банковской системы и приводятся основные элементы данной модели.